2019
DOI: 10.7759/cureus.6368
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Cost-effectiveness of LigaSure® in Total Thyroidectomy in Comparison with Conventional Suture Tie Technique

Abstract: Introduction: Total thyroidectomy has been considered to be a treatment of choice for thyroid malignancies. It has recently gained popularity as gold standard for benign thyroid disorders requiring surgical treatment. Because of higher number of complications associated with total thyroidectomy, it is still considered an adventurous endeavor. Most important improvements in thyroid surgery include laparoscopic thyroidectomy, energy based devices (EBD) like Harmonic Focus® and LigaSure® for dissection and hemost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Although more studies are needed in this context, a study showed lower mean operative time in patients who underwent thyroidectomy using the LigaSure™ rather than conventional clamp tie and electrocautery technique. [8] In a retrospective, observational study, the LigaSure™ usage resulted in lower blood loss and fewer blood transfusions and perioperative complications than suturing in the peripartum hysterectomy. [9] In another study, the LigaSure™ system reduced the volume of blood transfusions and intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Although more studies are needed in this context, a study showed lower mean operative time in patients who underwent thyroidectomy using the LigaSure™ rather than conventional clamp tie and electrocautery technique. [8] In a retrospective, observational study, the LigaSure™ usage resulted in lower blood loss and fewer blood transfusions and perioperative complications than suturing in the peripartum hysterectomy. [9] In another study, the LigaSure™ system reduced the volume of blood transfusions and intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…As regards operative times, shorter operations obtained using the energy-based devices rather than the traditional technique, as widely described in the literature [ 14 , 15 , 16 , 18 , 19 , 21 , 23 ], make it possible to increase the number of operations in the same surgical session, thus optimizing the utilization of the operating theatres and reducing the waiting lists. Furthermore, shorter operative times reduce anaesthesia times, allowing for faster recoveries after surgery, and decrease anaesthesia costs of each individual procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, several reports comparing the energy-based devices with the traditional technique exist. In most of these studies, Harmonic Focus and LigaSure Small Jaw (a device that works by means of advanced bipolar energy) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] were evaluated. Far fewer studies that compare the different devices with each other exist [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with these results, previous study enrolled 102 patients scheduled for thyroidectomy, up to 66.7% had multinodular goiter. There was only 1 studied case who had been diagnosed with differentiated thyroid cancer preoperatively (11) . In contrast, Back et al (12) studied 75 patients who underwent thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%